Platinum-DNA origami hybrid structures in concentrated hydrogen peroxide - Alarcón Correa, Mariana; Kilwing, Luzia; Peter, Florian; Liedl, Tim; Fischer, Peer (ChemPhysChem, 2023)
The DNA origami technique allows fast and large-scale production of DNA nanostructures that stand out with an accurate addressability of their anchor points. This enables the precise organization of guest molecules on the surfaces and results in diverse functionalities. However, the compatibility of DNA origami structures with catalytically active matter, a promising pathway to realize autonomous DNA machines, has so far been tested only in the context of bio-enzymatic activity, but not in chemically harsh reaction conditions. The latter are often required for catalytic processes involving high-energy fuels. Here, we provide proof-of-concept data showing that DNA origami structures are stable in 5 % hydrogen peroxide solutions over the course of at least three days. We report a protocol to couple these to platinum nanoparticles and show catalytic activity of the hybrid structures. We suggest that the presented hybrid structures are suitable to realize catalytic nanomachines combined with precisely engineered DNA nanostructures.